Posaconazole concentrations after allogeneic hematopoietic stem cell transplantation. Issue 5 (25th July 2013) - Heinz, W.J.; Einsele, H.; Helle‐Beyersdorf, A.; Zirkel, J.; Grau, A.; Schirmer, D.; Lenker, U.; Klinker, H.
Abstract Introduction Posaconazole is recommended for prophylaxis of fungal infections and for salvage therapy of invasive aspergillosis after stem cell transplantation. An impact of drug concentration on efficacy has been suggested. Methods In this study, we investigated serum levels of posaconazole in 262 samples from 64 allogeneic stem cell recipients. Results A high degree of interindividual variation was observed. Concentrations were significantly higher for male patients compared with female patients (median 570 and 426 ng/mL, respectively), but no differences for age or dosing groups (400 mg twice daily [BID] or 200 mg three times a day) could be detected. The predictive value of the first determined posaconazole concentration in steady state and of a concentration >500 and 700 ng/mL at any time was evaluated, compared with patients with a first level <300 ng/mL (mean 10.3%, median 0%). Conclusion In patients receiving 400 mg BID, the mean rate of serum levels >500 ng/mL in subsequent determinations was higher, if the first serum concentration during steady state was >300 ng/mL (mean 61.1%, median 60%, P = 0.002) or >500 ng/mL (67.7%, median 75%, P = 0.002). Based on this retrospective analysis, a posaconazole serum concentration >500 ng/mL at any time point might also help to predict sufficient drug concentrations.